RELIGIOUS TOLERANCE IN THE SUGDIYANA REGION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article provides detailed information about the history of religious tolerance in the Sugdiyana region, its current status and its role in social life. Important factors in ensuring religious tolerance in the region and their impact on social stability are considered.